PENGARUH LOKASI USAHA DAN KREATIVITAS TERHADAP KEBERHASILAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) PENJAHIT PAKAIAN DI KECAMATAN BATURAJA TIMUR - Roby Yansyah; Yopi Yunsepa; Hema Malini (STIE DWI SAKTI BATURAJA, 2023)
This research is entitled Effect of business location and creativity on the success of micro, small and medium enterprises (MSMEs) tailoring clothes in East Baturaja. The purpose of this study was to determine the effect of business location and creativity on the success of clothing tailoring micro, small and medium enterprises (MSMEs) in East Baturaja sub-district. The research method used is descriptive research method. Based on the results of the research that has been done, the multiple linear regression equation is Y = 2.921 + 0.177X1 + 0.610X2 The tcount value of the business location variable (X1) is 0.811 and ttable is 2.0639 where tcount < ttable (0.811<2.0639), then H0 is accepted and Ha is rejected, meaning that there is no effect of business location on the success of the tailoring business in Baturaja Timur. And the tcount value of the creativity variable (X2) is 1.971 and t table is 2.0639 where tcount < ttable (1.97 <2.0639), then H0 is accepted and Ha is rejected, meaning that there is no effect of price on the success of the tailoring business in BaturajaTimur . The Fcount value is 3.837 and the Ftable value is 3.40. So Fcount > Ftable where 3.837 > 3.40 then H0 is rejected and Ha is accepted, meaning that there is influence between business location (X1) and creativity (X2) together on the variable success of the tailoring business in East Baturaja